Keamanan dan Keselamatan Implementansi Internet Of Things (IoT): Tantangan pada Sektor Industri dan Rumah Tangga - Muhammad Tengku Sadewa; Tata Sutabri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The rapid development of the Internet of Things (IoT) has transformed various aspects of industrial and household activities by enabling interconnected devices to communicate and exchange data through internet networks. IoT technology supports automation, real-time monitoring, and intelligent decision-making, thereby improving operational efficiency, productivity, convenience, and security. In the industrial sector, IoT contributes to predictive maintenance, production optimization, and resource management, while in households it facilitates smart home systems that enhance energy efficiency, comfort, and safety. Despite these benefits, the widespread adoption of IoT continues to face several challenges, including data security and privacy concerns, interoperability among devices, infrastructure limitations, high implementation costs, and varying levels of digital literacy among users. This study employs a qualitative approach using phenomenological research to explore and understand the experiences, perceptions, and challenges encountered in the implementation of IoT technologies in both industrial and household environments. By examining these experiences, the study provides a comprehensive understanding of how IoT is adopted in practice and identifies the factors influencing its successful implementation. The findings are expected to contribute to the development of more effective IoT implementation strategies and support future technological innovation in the era of digital transformation.